Firms and the global crisis: French exports in the turmoil - Jean-Charles Bricongne; Lionel Fontagné; Guillaume Gaulier; Daria Taglioni; Vincent Vicard (European Central Bank (ECB), 2010)
Global trade contracted quickly and severely during the global crisis. This paper, using a unique dataset of French firms, matching together export data with firm-level credit constraints, shows that most of the 2008-2009 trade collapse is accounted by the unprecedented demand shock and by product characteristics. While all firms have been evenly affected by the crisis, large firms did so mainly through the intensive margin and by reducing the portfolio of products offered in each destination served. Smaller exporters instead have been forced to reduce the range of destinations served or to stop exporting altogether. Credit constraints, on their part, emerged as an aggravating factor for firms active in sectors of high financial dependence. Nonetheless, as the share of credit constrained firms is small and their number did not increase much during the crisis, the overall impact of credit constraints on trade remains limited.
Keywords: F02; F10; G01; 330; credit constraints; financial crisis; firms' heterogeneity; intensive and extensive margins; international trade; Finanzkrise; Kreditrationierung; Handelseffekt; Exportwirtschaft; Frankreich